Prognostic value of immunohistochemical surfactant protein A expression in regenerative/hyperplastic alveolar epithelial cells in idiopathic interstitial pneumonias - Kajiki Akira; Fukushima Kazuo; Kawabata Masaharu; Wakamatsu Kentaro; Kitasato Yasuhiko; Nagata Nobuhiko; Kitahara Yoshinari; Watanabe Kentaro (BMC, 2011)
Abstract Background It is difficult to predict survival in patients with idiopathic pulmonary fibrosis. Recently, several proteins, such as surfactant protein (SP) and KL-6, have been reported to be useful biologic markers for prediction of prognosis for interstitial pneumonias. It is not clear whether there is any relationship between expression of these proteins in regenerative/hyperplastic alveolar epithelial cells and prognosis of idiopathic interstitial pneumonias (IIPs). Objectives This study aimed to elucidate the clinical significance of the expression of such lung secretory proteins as SP-A and KL-6 in lung tissues of patients with IIPs. Methods We retrospectively investigated the immunohistochemical expression of SP-A, KL-6, cytokeratin (CK), and epithelial membrane antigen (EMA) in alveolar epithelial cells in lung tissues obtained from surgical lung biopsy in 43 patients with IIPs, and analyzed the correlation between expression of these markers and the prognosis of each IIP patient. CK and EMA were used as general markers for epithelial cells. Results In patients with usual interstitial pneumonia (UIP), the ratio of SP-A positive epithelial cells to all alveolar epithelial cells (SP-A positive ratio) in the collapsed and mural fibrosis areas varied, ranging from cases where almost all alveolar epithelial cells expressed SP-A to cases where only a few did. On the other hand, in many patients with nonspecific interstitial pneumonia (NSIP), many of the alveolar epithelial cells in the diseased areas expressed SP-A. The SP-A positive ratio was significantly lower in patients who died from progression of UIP than in patients with UIP who remained stable or deteriorated but did not die. In NSIP patients, a similar tendency was noted between the SP-A positive ratio and prognosis. Conclusions The results suggest that the paucity of immunohistochemical SP-A expression in alveolar epithelial cells in diseased areas (i.e. regenerative/hyperplastic alveolar epithelial cells) may predict a worse prognosis for patients with IIPs, especially patients with UIP. A prospective study is needed to confirm these results.